PENGARUH DUKUNGAN ORGANISASIONAL TERHADAP KEPUASAN KERJA DAN MOTIVASI KERJA ANGGOTA UNIDADE PATRULHAMENTU FRONTEIRA (UPF) DI PERBATASAN MOTA’AIN – BATUGADE TIMOR LESTE - Martins, Armando Dos Santos; Sintaasih, Desak Ketut (Buletin Studi Ekonomi; VOL.23.NO.2.AGUSTUS 2018, 2019)
Abstract  -  This research was conducted to examine the effect of organizational support against the job satisfaction and work motivation against the members of Border Patrol Unit .   The populations were 327. However the researcher defined to have a 60 members of the unit as a sample which only focus on the ranks of Ajente, Ajente Prinsipál, Ajente Xefe a nd  First Sergeants .  This research  were  uses a quantitative and quantitative approach  and desriptif methods  against the items  were be  tested and described by using the average value and the percentage score  by using the  Smart Partial Least Square (PLS)  approach .The Results of this research  was  shown that, the Organization Support against the job satisfaction  and work  motivation  as well as the job satisfatin against the work motivatin  of members were positive  and  significant effected on member’s work motivation.   Keywords: Organizational  Support, Job Satisfation and Work Motivation